Peran Locus dan Tempus Delicti dalam Menentukan Kompetensi Pengadilan pada Kasus Kejahatan Siber - Balla, Herman; Jumardin , Jumardin; Kasim, Aksah; Kala Pappa, Abraham (Jurnal Litigasi Amsir, 2024)
This study aims to analyze the determination of locus and tempus delicti in cybercrime cases and their influence on court competence and law enforcement effectiveness. The research method used is normative research with a legislative approach. The results of the study show that the determination of locus and tempus delicti in cybercrime becomes complex because these crimes can be carried out from various different locations and at times that are difficult to determine with certainty. Several theories can be used to determine locus delicti, such as the theory of material action, the theory of tools used, and the theory of effect. Tempus delicti can be determined by looking at file logs or activity logs in the computer system. The determination of locus and tempus delicti greatly affects the competence of the court and the validity or not of the indictment. Further research, comprehensive policy development, international cooperation, and criminal law updates relevant to technological developments are needed to address these challenges and ensure effective and fair law enforcement against cybercrime.